James Ensor, occasional modernist Ensor's artistic and social ideas and the interpretation of his art - Todts, Herwig 1958- (Brepols, 2018)
In the course of the twentieth century, under the influence of the increasing success of Modernism, a misleading image of James Ensor emerged. One might even say that Ensor was confined within a modernist "straitjacket". In order to understand the artist's motivations, this book follows the advice given to the art critic Andre De Ridder by Ensor himself in 1930: "I recommend you re-read 'Les Écrits de James Ensor', where I explain my research and defend my ideas". Ensor's writings can roughly be divided into two categories, his letters and "les écrits", encompassing his journalistic work, satirical exhibition reviews, comical speeches, words of thanks and praise, and open letters in brochures. The analysis of Ensor's writings is no small task, for he gave little attention to structure and coherence, and employed a complex "wondermiraclelikefulistic" language-archaisms, neologisms, staggering vitriolic rants, hyperboles. Nevertheless, his writings are a crucial source of knowledge on his opinions on Christian faith, rationality, hypocrisy, the dangers of an emerging Flemish nationalism, animal cruelty, the destruction of natural beauty and ancient monuments, and a number of other topics.
Bandangabe von der Website des Verlags ermittelt
Keywords: Ensor, James -- 1860-1949; Biografie